Evaluation of Nutritional Quality of Dried Cashew Nut Testa Using Laboratory Rat as a Model for Pigs - Armstrong Donkoh; Victoria Attoh-Kotoku; Reginald Osei Kwame; Richard Gascar (The Scientific World Journal)
Dried cashew nut testa (DCNT) was characterized with respect to proximate, mineral, and energy profile. The crude protein, crude fibre, and fat and ash contents were, in g kg−1 DM, 190.0, 103.0, 20.1, and 20.2, respectively, with metabolizable energy of 7.12 MJ kg−1 DM. In a feeding trial, isoproteic diets containing DCNT (O, 50, 100, and 150 g kg−1) were fed ad libitum to 4 groups of Sprague-Dawley male rats (110 g body weight, 𝑛=20) for a period of 4 weeks. The rats, used as model for pigs, had free access to water. As the dietary DCNT content was increased from 0 to 150 g kg−1, there was a significant (𝑃<0.01) decrease in feed intake (𝑟=−0.99), water intake (𝑟=−0.87), and a reduction in body weight gain (𝑟=−0.93) and efficiency of feed utilization (𝑟=0.78). However, no deaths or health-related problems were recorded during the study. Dietary treatments had no impact on liver, heart, lungs, kidneys, and intestinal weights. Cost per gram feed and feed cost per gram live weight gain were reduced when DCNT was used. The experimental diet containing 50 g DCNT kg−1 supported the best growth performance with the lowest feed cost per gram live weight gain of GHȼ0.18. Seasonal increases in the prices of conventional feedstuffs like maize and fishmeal would make the use of agroindustrial by-products such as DCNT in pig diets even more attractive.